Clinical and Biochemical Studies of the Gender Specific Risk Factors for Cssardiovascular Disease in Patients of Type 2 Diabetes with NAFLD (The Insight, 2023)
Introduction: Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality in individuals with type 2 diabetes mellitus (T2DM). Additionally, the co-occurrence of non-alcoholic fatty liver disease (NAFLD) further exacerbates this risk. While numerous studies have explored the pathophysiological mechanisms underlying CVD in T2DM, there is a notable paucity of research focusing on the gender-specific nuances of this complex interplay.  Methods & Materials: A hospital-based observational study was carried out in the Department of Medicine, Cumilla Medical College and Hospital, Bangladesh, from 1st July to 31st December 2012. Fifty admitted patients of type2 diabetes with NAFLD were included in this study.  Results: Out of 50 patients, 18(36%) were males and 32(64%) were females, with mean age 58.89 ± 8.38 and 54.6 ± 10.1 years respectively. The prevalence of hypertension (p
Keywords: Non-alcoholic fatty liver disease; cardiovascular disease; metabolic syndrome; cardiovascular risk factors